Analisis Pengembangan Objek Wisata Gunung Telomoyo Sepakung Kecamatan Banyubiru Kabupaten Semarang - Maesa Rizal Meilano; Purnomo Adi Saputro (Journal of Creative Student Research, 2026)
Mount Telomoyo, located on the border of Magelang and Semarang Regencies, has a unique attraction: tourists can access its summit directly by vehicle. The route through Sepakung Village has become an increasingly popular alternative due to its beautiful natural scenery and strong local cultural values, offering significant tourism development potential. However, tourism management has not been optimized, necessitating strategic development planning. This study aims to identify the potential and existing challenges of the Mount Telomoyo tourist attraction in Sepakung Village and to analyze appropriate development strategies. This study used a quantitative descriptive method, with data collected through observation, interviews, and documentation. The analysis was conducted using tourism potential scoring and tourism development strategy scoring. The findings indicate that Mount Telomoyo offers a unique natural attraction, allowing visitors to reach the summit by motorbike, motorcycle taxi, or jeep while enjoying views of the forest, plantations, and surrounding mountains such as Mount Merbabu and Mount Andong. The scoring results classify the tourism potential and its management as high. The SWOT analysis places the destination in Quadrant IV, indicating a defensive/diversification strategy. This study recommends that the Sepakung Village government play an active role in promoting community-based tourism by improving road and evacuation infrastructure and increasing the capacity of local human resources through training and guidance.